Evaluation of Interfacial Tension in The Liquid Aluminum Alloy – Liquid Slag System - Suchora-Kozakiewicz, Magdalena; Jackowski, Jacek (Journal of Casting & Materials Engineering, 2017)
In the present paper, there are presented the results of investigations of the interfacial tensions present at the borders of the liquid aluminum alloy and two selected melted fluxes (mixtures of salts). The fluxes featured with the solidification characteristic curves very close to each other and the differentiated chemical compositions. For the comparative investigations, the so called surface property index, WS, calculated for both fluxes, with use of the ion theory of slags. The investigations of the interfacial tensions were conducted on a stand enabling the measurement the force values accompanying tearing-off of the probe from the interfacial surface. A very clear relation between the interfacial tension values and the WS index values, characterizing both fluxes, was found. An increase of the WS index value resulted in an increase in of the investigated interfacial tension values. It was found, also that, in both cases under investigation, an increase of the system temperature value, resulted in an increase o the values of the interfacial tensions present in it. In the conclusion, it was stated that the metallurgical treatments, for instance the recycling of the cast metal composite materials on the way of component separation should conducted with use of salt mixtures (fluxes) characterized with the WS index value as low as possible and, also, a low melting temperature value.